ANALISA KUALITAS LAYANAN JARINGAN INTERNET BERBASIS WIRELESS LAN - Aman, Robertus; Gunawan, Putu Wida; Bernadus, I Nyoman (J-Icon : Jurnal Komputer dan Informatika, 2024)
Educational institutions certainly have the same hope of establishing a good internet service system in order to realize mutual satisfaction in the academic environment. In reality, not all educational institutions have achieved this, of the many institutions Tunas Daud School is one of them. Results of observations that have been carried out previously are problems that often occur today, complaints about internet network disruptions are still often experienced at certain times when downloading or uploading data. The aim of the research is to analyze the Quality of Service (QoS) on the Tunas Daud School internet network. The results of this research will describe the customer satisfaction index (CSI) method, also known as the customer satisfaction index, which means the weight of school internet user satisfaction with a total average satisfaction index of 61.93% (quite satisfied), with a value for each throughput parameter of 76.52% (satisfied), delay 40.85% (dissatisfied), packet loss 52.31% (quite satisfied), jitter 69.14% (satisfied), and bandwidth 37% (dissatisfied).